Probabilistic Aspects of Main Oil and Gas Pipelines Connections Calculation - Nesterenko Sr., Tatyana; Lartseva, Iryna; Kaliuzhnyi, Anatolii; Yaholnyk, Andrii (International Journal of Engineering and Technology, 2018)
The article analyzes the existing calculation methods and highlights the main stages of main pipelines flanged connections calculation. A logical-structural scheme for the pipeline connection destruction is proposed. On the basis of the scheme developed, the analysis of usual flange connection destruction was carried out. As a result, formulas for determining safety characteristics of connection elements and equations for determining the failure-free operation probability for both individual elements of the connection and the connection as a whole were obtained.Â Â